The role of social support in serving Covid-19 patients (A descriptive study applied on those who recovered from Corona virus and social workers in health centers in Tataman clinics in Turbah Province) - Albugam, Humod Ayed (Journal of Humanities & Social Sciences, 2022)
This study aimed to identify the role of the social worker in providing social support to Covid- 19 patients, to identify the relationship between social support and the psychological, social and economic effects of Covid- 19 patients, and to identify the main impediments to the functioning of clinical social service in dealing with victims of the Corona virus. The study belongs to the pattern of descriptive studies, which were based on the social survey course of the sample, and the study sample consisted of two categories: The first category consisted of 150 beneficiaries and auditors of health centers in clinics in the Turabah Governorate, and the second category consisted of 32 social workers working in health centers in clinics in the Turabah Governorate.The study produced a series of findings, the most important of which were: One of the most important effects of the Corona pandemic (fear of transmission to the family, feeling of psychological stress due to quarantine, feeling of psychological isolation during the period of injury, inability to adapt to the conditions of domestic quarantine). The study also showed that one of the most important roles of the social worker in providing social support to Covid- 19 patients was to prepare the patient and remove his fears, as well as to provide the medical team with social information on the situation.The study recommended that on- the- job training courses should be provided on a continuous basis to inform clinical social workers of the latest trends and methods of general social service practice in the medical field.
Keywords: Corona virus; social service; pandemic; social support